Sol-gel hydrothermal synthesis of bismuth-TiO2 nanocubes for dye-sensitized solar cell - An'amt, M.N.; Radiman, S.; Huang, N.M.; Yarmo, M.A.; Ariyanto, N.P.; Lim, H.N.; Muhamad, M.R. (2010)
Bismuth-TiO2 nanocubes were synthesized via a facile sol-gel hydrothermal method with titanium tetraisopropoxide as the precursor. The influence of the bismuth on the size, morphology, crystallinity and optical behavior of TiO2 nanocubes were investigated. The samples were characterized by X-ray diffraction analysis (XRD), transmission electron microscopy (TEM), energy dispersive X-ray (EDX), field emission scanning electron microscopy (FESEM) and UV-visible spectroscopy (UV-vis). Photovoltaic behavior of dye-sensitized solar cells (DSSCs) fabricated using Bi-TiO 2 nanocubes was studied. The DSSCs had an open-circuit voltage (Voc) of 590 mV, a short-circuit current density (Jsc) of 7.71 mA/cm2, and the conversion efficiency (Î·) of 2.11 under AM 1.5 illumination, a 77 increment as compared to pure TiO2 nanocubes. Â© 2010 Elsevier Ltd and Techna Group S.r.l. All rights reserved.